Knowledge on Prevention of Carcinoma Cervix among Women in the Reproductive Age Group at Kokilamedu Village, Kanchipuram District, Tamil Nadu (Medico Legal Update, 2020)
The knowledge on prevention of Carcinoma Cervix among the reproductive age group women in Kokilameduvillage at Kanchipuram District, Tamil Nadu, India. The objectives were to assess the knowledge onprevention of Carcinoma Cervix among women in Kokilamedu village at Kanchipuram District, Tamil Naduand to find out the association between the level of knowledge with demographic variables. The conveniencesampling was used to select 104 samples of reproductive age group women. The data collection tools werevalidated and reliability was established. The data were collected by self administered questionnaire. Thecollected data was tabulated and analyzed. Descriptive and inferential statistics method were used. Thestudy shows that 45% of the women had poor knowledge, 59% of the mothers had moderate knowledgeand non of the women had adequate knowledge regarding prevention of Carcinoma Cervix. There was nosignificant association between the knowledge and the selected Demographic Variables.